Profiling Alternative 3′ Untranslated Regions in Sorghum using RNA-seq Data - Tu, Min; Li, Yin (Frontiers in Genetics, 2020)
Translation, transport and stability of messenger RNA are regulated by 3’ untranslated region (3’UTR). Alternative polyadenylation, a phenomenon known to produce alternative 3’UTR, has been characterized in Arabidopsis using specialized sequencing methods targeting poly(A) sites. Such approaches are technically challenging and require robust bioinformatic skills, leaving few reports on large-scale 3’UTR profiling in crops. Since a dominant portion of the public RNA-seq samples in crops have been conducted in Illumina short-read platforms, alternative 3’UTR study using conventional RNA-seq data is critical for agriculturally important crops, like sorghum. Here, employing priUTR, a 3’UTR pipeline integrable with the classic RNA-seq analysis pipelines, we present transcriptome-wide alternative 3’UTR profiles in three genetically related but phenotypic contrast lines of sorghum. Data-driven analysis of sorghum alternative 3’UTRs yields novel insights and generates testable new hypotheses for 3’UTR-mediated gene regulation. Surprisingly, the alternative-3’UTR genes significantly overlaps with those that could be modified by RNA N6- methyladenosine (m6A), suggesting a link between m6A and alternative 3’UTR. Moreover, taking advantage of sorghum genetics, we provide evidence of genotype specificity of alternative 3’UTR usage. In summary, our work characterizes the alternative 3’UTRs in sorghum at the transcriptome-wide level, demonstrates feasibility to profile alternative 3’UTRs through conventional RNA-seq in non-model plants and signifies 3’UTR analysis as a valuable addition to routine RNA-seq data analysis.